Effect of Physical Activity Education on Reducing Low Back Pain and Improving Exercise Attitude Among Pregnant Women - Yuni Astuti; Adelia Priska Amanda (Universitas Muhammadiyah Semarang, 2026)
Low back pain (LBP) is a prevalent musculoskeletal complaint during pregnancy, associated with physiological and biomechanical changes that limit daily activity. Structured physical activity and educational interventions have shown benefits in reducing pain and improving maternal attitudes toward exercise. The aim of this study was to evaluate the effect of physical activity education using a booklet on the incidence of LBP and attitudes towards physical activity among pregnant women. This quasi-experimental study employed a one-group pretest-post-test design without a control group. Participants included 33 pregnant women in the second and third trimesters attending a primary health centre in Bantul, Yogyakarta, Indonesia. A pretested questionnaire was used to collect data on the sociodemographic characteristics, the occurrence of low back pain, and the attitude towards physical activity during pregnancy. The intervention consisted of structured physical activity education using a handbook containing recommended prenatal exercises, ergonomic guidance, and safe practice tips, delivered over three weeks. Data were analysed using the Wilcoxon signed-rank test with significance level α=0.05. A total of 29 respondents were included in the study. The median LBP score decreased from 5 to 2 post-intervention (Z = -4.737, p < 0.001). The proportion of participants with a positive attitude towards physical activity increased from 37.9% to 89.7% (Z = -3.638, p < 0.001). Physical activity education using a booklet effectively reduced the intensity of LBP and improved the physical activity attitudes of pregnant women. Integration of structured exercise education into antenatal care services is recommended to promote maternal comfort